Gene loss and co-option of toll-like receptors facilitate paternal immunological adaptation in the brood pouch of pregnant male seahorses - Zhang, Bo; Xiao, Wanghong; Qin, Geng; Chen, Zelin; Qiu, Lihua; Wang, Xin; Lin, Qiang (Frontiers in Immunology, 2023)
Male pregnancy in syngnathids (seahorses, pipefishes, and sea dragons) is an evolutionary innovation in the animal kingdom. Paternal immune resistance to the fetus is a critical challenge, particularly in seahorses with fully enclosed brood pouches and sophisticated placentas. In this study, comparative genomic analysis revealed that all syngnathid species lost three vertebrate-conserved Toll-like receptors (TLR1, TLR2, and TLR9), of which all play essential roles in immune protection and immune tolerance in the uterus and placenta. RT-qPCR analysis showed that the TLR paralog genes including TLR18, TLR25, and TLR21 were highly expressed in the placenta inside the seahorse brood pouch and changed dynamically during the breeding cycle, suggesting the potentially important role of the TLRs during male pregnancy. Furthermore, the immune challenge test in vitro showed a remarkable expression response from all three TLR genes to specific pathogenic antigens, confirming their immune function in seahorse brood pouches. Notably, the altered antigen recognition spectrum of these genes appeared to functionally compensate in part for the lost TLRs, in contrast to that observed in other species. Therefore, we suggest that gene loss and co-option of TLRs may be a typical evolutionary strategy for facilitating paternal immunological adaptation during male pregnancy.